Design and performance enhancement of a bi-directional counter-rotating type horizontal axis tidal turbine. (1st December 2016) - Huang, B.; Zhu, G.J.; Kanemoto, T.
Abstract: A bi-directional counter-rotating type horizontal axis tidal turbine (HATT) consisting of fully symmetrical hydrofoils was designed to convert tidal energy in terms of ebb and flood tides. In CFD simulations, the counter-rotating rotors perform much more excellent power coefficient than single rotor. However, as the limit of application of fully symmetrical hydrofoils with low lift-drag ratio, the performance of bi-directional HATTs is much lower than traditional HATTs. In this work, multi-objective optimization method was employed to obtain a series of fully symmetrical hydrofoils applied to different sections from blade root to tip. The numerical results show that the application of optimized hydrofoils brings about considerable increment in power efficient (a relative increase 8% at BEP) and flow separation around hydrofoil. Highlights: A bi-directional counter-rotating type horizontal axis tidal turbine was proposed. A series of symmetrical hydrofoils were developed for bi-directional turbines. Counter-rotating rotors show much higher Cp than single rotor. Performance enhancement has been achieved by optimization of hydrofoils.